Meningkatkan Keterampilan Berpikir Kreatif Siswa: Implementasi Rbl-Stem Dalam Mengembangkan Urban Farming “Bananaponik” - Okti Anis Safiati; Rini Purwaningtyas; Siti chususiyah; Diana Puji Lestari; Ida Fitriati; Dafik (Desanta Publisher, 2024)
Students' creative thinking abilities are very important in the current era. In an ever-changing world with complex problems and challenges, creative thinking skills enable individuals to generate innovative solutions, think outside the box, and adapt to new situations effectively. Despite the importance of creative thinking skills, there are challenges in fostering and developing creative thinking skills among students. Many traditional education systems prioritize memorization and standardized tests over creativity and critical thinking. This can limit opportunities for students to develop and practice their creativity. To address this, it is necessary to integrate more creative and research-based learning activities into the classroom, allowing students to engage in multiple project assignments. In this research, we implemented the Research Based Learning (RBL) model together with a STEM approach to involve students in bananaponics urban farming development project tasks. Students were given the task of planning to plant several types of vegetables on banana stems in the school backyard and grouping them in two weeks. The results of this research are in the form of a STEM problem formulation, integration of RBL_STEM syntax and including a description of four STEM studies, and finally the development of an assessment instrument for increasing students' creativity abilities.